Mastering Teacher Competencies through Collaborative Multimodal Teaching - Vina Nurviyani; Halimah Halimah; Asep Saepuloh; Anisa Sofarini (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study explored how student teachers master teacher competencies through collaborative multimodal teaching. In this case, the teaching-learning processes focused on vocabulary. Moreover, it investigated the difficulties encountered by student teachers in mastering teacher competencies through collaborative multimodal teaching. Teacher competencies cover pedagogical, professional, social, and personal (Ministry of National Education, 2007). This study applied qualitative design (multi-case study) involving 45 student teachers studying at three different study programs and 15 model teachers teaching at elementary schools in Cianjur, West Java. Three instruments were employed for the data collection of this study, i.e., observations, questionnaires, and interviews. The results indicate that collaborative multimodal teaching among the model teachers and the student teachers is conducted in five stages, i.e., observing, planning, simulating, practicing, and evaluating. In collaborative multimodal teaching, student teachers and model teachers are involved in groups of teaching using multimodal instructional media (e.g., VR) to apply the pedagogical knowledge and practice multimodal teaching directly in the natural teaching-learning processes.